Pengaruh Mental Work Load dan Gejala Post-Traumatic Stress Disorder (PTSD) Terhadap Kinerja Petugas Rescue di PT Freeport Indonesia - Suryanto, Sony T.; Maarif, M. Syamsul; Baga, Lukman M. (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
The purpose of this study is to analyze the relationship between mental workload and Post-Traumatic Stress Disorder (PTSD) symptoms to the performance of PTFI rescue officers. The analysis includes descriptive analysis, bivariate analysis using Chi Square test, and Structural Equation Model (SEM) analysis using Partial Least Squares (PLS) program. The calculation of the data shows that PTFI rescue officers have a high overall mental workload perception, the prevalence of PTSD symptoms is 10.48%, and the overall average performance is appraised as meet expectations. The results of the SEM-PLS analysis shows that mental workload has a significant effect on performance (p-values 0.045 sig.5%) and PTSD symptoms have no effect on performance (p-values 0.885 sig.5%) but has a significant effect on mental workload (p-values 0.026 sig.5%). The Chi Square test shows a significant correlation between the predictor of assignment location with PTSD symptoms (p-values 0.019 sig.5%) and performance (p-values 0.032 sig.5%). The managerial implications then proposed to obtain healthy mental and optimal productivity of PTFI rescue officers, including handling PTSD symptoms, facilitating coping strategies, analyzing the influence of competence to mental workload, implement structured program to deal with traumatic events exposure, measuring the stress level, and measuring behavioral elements that support employees' perceptions as citizen of the organization. Keywords: mental workload, performance, PTSD symptoms, rescue officer